“He Fell in and That's How He Became a Fossil!”: Engagement With a Storytelling Exhibit Predicts Families' Explanatory Science Talk During a Museum Visit - Callanan, Maureen A.; Castañeda, Claudia L.; Solis, Graciela; Luce, Megan R.; Diep, Mathew; McHugh, Sam R.; Martin, Jennifer L.; Scotchmoor, Judy; DeAngelis, Sara (Frontiers in Psychology, 2021)
Parent-child conversations in everyday interactions may set the stage for children’s interest and understanding about science. Studies of family conversations in museums have found links to children’s engagement and learning. Stories and narratives about science may spark children’s interest in science topics. This study asks whether a museum exhibit that provides opportunities for families to create narratives might encourage families’ explanatory science talk throughout the rest of the exhibit. The project focused on the potential impact of a hands-on story-telling exhibit, the “spin browser” embedded within a larger exhibition focused on fossilized mammoth bones – Mammoth Discovery! at Children’s Discovery Museum of San Jose. Participants were 83 families with children between 3 and 11 years (mean age 7 years).We coded families’ narrative talk (telling stories about the living mammoth or the fossil discovery) and connecting talk (linking the story to other nearby exhibits) while families visited the spin browser, and we also coded families’ explanatory science talk at the exhibits that contained authentic fossil bones and replica bones. The parents in families who visited the spin browser (n=37) were more likely to engage in science talk at the fossil exhibits than those in families who did not visit the spin browser (n=46). Further, a regression analysis showed that family science talk at the fossil exhibits was predicted by parents’ connections talk and children’s narrative talk at the spin browser. These findings suggest that families’ narratives and stories may provide an entry point for science-related talk, and encourage future study about specific links between storytelling and science understanding.